Fatores controladores de Najas arguta Kunth e Egeria densa Planch em um reservatório do semiárido do Brasil - Lycarião, Thainá Alves (2015)
Understanding the dynamics of ecosystems in semiarid regions with dry and wet extremes may help elucidate issues related to the existing pattern of interaction in these environments, and these relationships can affect the ecological interactions of organisms present in the water body. Thus, this study aimed to determine the abiotic variables that act in development of Najas arguta (Kunth) and Egeria densa (Planch), highlighting how these variables influence the relationship of the two submerged macrophytes in a reservoir in semiarid region. N arguta biomass data and E. densa were obtained in six stands, located three out of the reservoir shoreline. In each stands is selected parcels 100x50 meters, which have been measured abiotic data and collected plants through cross hooks (cor er ) 0.5m in diameter (n = 4) at depths 1m, 2m and 3m. Analysis of Variance (ANOVA) factor a + b was used to test the seasonal and spatial variation of stands and environmental variables, linear regression analysis was used to understand the dependence of N. arguta and E. densa . Generalized Linear Models (GLM) were used to select environmental variables that explain the occurrence of N. arguta , E. densa and its relationship (Najas:Egeria ). Abiotic data showed low coefficients of temporal variation (<30%) due to continued drought conditions. N. Arguta presented a variation of biomass between the months of August / 13 and April / 14, with totals of 25.67 g.m-² and 1.06 g.m-², respectively. While E. densa maintained high biomass in the entire study period. The submerged plants had different niches, showing that E. densa competition relationship with N. arguta . The predictive model for biomass of N. arguta showed that physical and chemical variables had more influence in their biomass, whereas physical, chemical and climatic variables were related more to the biomass of E. densa . The relationship Najas Egeria was influenced by conductivity, total dissolved solids and nitrite. For presenting adaptations to the conditions of the reservoir, E. densa kept his high biomass, occupying more favorable niches and suppressing the development of N. arguta .